Uncertainty and firms' labour decisions: Evidence from European countries - Marta Martinez-Matute; Alberto Urtasun (Journal of Applied Economics, 2022)
Uncertainty affects employers' decisions about their workforce as well as capital. We exploit differences in how firms change the size of their workforce when uncertainty increases. Using data from the Wage Dynamic Network Survey for 25 European countries, we first construct, unlike the usual aggregate indicators, a set of uncertainty indicators exploiting each firm's microeconomic environment. We combine variability from the country, sector and size of the firm. Secondly, we investigate the effect of uncertainty on a firm's strategies to adjust labour through hiring and firing. The results reveal that firms reduce hiring and recur to individual layoffs more frequently when uncertainty increases. An increase of one standard deviation in the uncertainty indicator is associated with an increase in the probability of having frozen hiring by from 9% to 16% of a standard deviation. We also find more significant effects when firms face credit constraints and labour adjustment costs are higher.
Keywords: 330; firms' labour decisions; hiring freezes; labour adjustment; layoffs; Uncertainty